The Influence of marketing mix strategies on the business performance of Small and Medium Enterprises in Nairobi central business district - Mwachiro, A. M. (Strathmore University, 2025)
Performance refers to the outcomes achieved by individuals, teams, or organizations regarding output, efficiency, and effectiveness (Armstrong 2017). Schermerhorn Jr., Bachrach, and Wright (2020) also defined performance as the measure of how well the business and individuals can achieve their goals and objectives. Steers, Bigley, and Porter (2021) support the definition made by Schermerhorn Jr by defining performance as the degree to which an individual or organization achieves its goals and meets shareholders' expectations. The study will focus more on how performance satisfies the customers' needs and achieves the goals set by the organization or business. Kotler and Keller (20 16) suggest that marketing encompasses the identification and fulfillment of human and social needs, as well as the creation of value for customers and the establishment of strong customer relationships to gain value in return. Marketing involves the activities, institutions, and processes for creating, communicating, delivering, and exchanging offerings that have value for customers, clients, partners, and society at large (Solomon 20 17). Businesses can satisfy various customer needs by carrying out marketing promotions through planning, execution, and supervision (O'Cass, Ngo, & Siahtiri,2012). Small and Medium Enterprises (SMEs) are increasingly understanding the need to establish their marketing strategies to enable them to have a broad understanding of the environment, customers, and the needs of their customers.
Full - text undergraduate research project